Analisis Putusan Pengadilan Agama Kotabumi Nomor 767/Pdt.G/2024/Pa.Ktbm Terkait Hak Asuh Anak Berdasarkan Hasil Kesepakatan Perdamaian Sebagian Dihubungkan Dengan Prinsip The Best Interest Of Child - Shavira Ayundara Wiraningrat; Rai Mantili; Betty Rubiati (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the legal reasoning and normative implications of the Religious Court Decision of Kotabumi Number 767/Pdt.G/2024/PA.Ktbm concerning child custody determined through a partial settlement agreement, analyzed in light of the principle of the best interest of the child. Employing a normative juridical method with statute and case approaches, this research analyzes relevant legal frameworks, including Indonesian Marriage Law, Child Protection Law, and Supreme Court Regulation on mediation, alongside doctrinal perspectives and judicial practices. The findings reveal that while the decision reflects formal compliance with mediation-based dispute resolution and acknowledges the principle of the best interest of the child, its substantive application remains limited by the absence of structured judicial reasoning and insufficient articulation of child-centered considerations. Furthermore, the enforceability of such decisions is constrained by normative gaps in post-judgment supervision and execution mechanisms. This study proposes a reconstruction of legal norms to strengthen judicial oversight and ensure that custody decisions effectively safeguard children's rights in both declarative and practical dimensions.